(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
From a notion of “theater of states”, we propose in this article to present some reflections on the main categories used by the Argentine theater director Ricardo Bartís. How does Bartís re-elaborate Alberto Ure’s “theater of states”? How does Bartís articulate in his workshops the director’s dramaturgy and the construction of conventions from objects? We will reconstruct the main guidelines of the acting training offered by Bartís. We are also interested in briefly reconstructing the work Argentine Postcards (1988) to understand how some fundamentals of Bartís poetic construction operate in a finished work, emphasizing the construction of conventions.